THE SUCCESS RATE OF TUBERCULOSIS SURVEILLANCE IN THE REGENCY OF ACEH BARAT - Khairunnas,; Yarmaliza,; Farisni, Teungku Nih; S, Susy Sriwahyuni; Zakiyuddin, (International Journal of Psychosocial Rehabilitation, 2020)
One of the successful tuberculosis (TB) countermeasures is the achievement of a Case Detection Rate with a national standard of at least 70%. In 2018 the Regency of Aceh Barat CDR achievement is still very low (25.39%). The success of TB surveillance is inseparable from the components inherent in surveillance. The purpose this study was to look at the relationship between input components (HR and facilities), processes (data collection) and outputs (cross-sectoral feedback) with the success of TB surveillance in Regency of Aceh Barat. The research method was observational analytic with cross sectional study design in which there were 13 respondents who were responsible for the TB program with univariate and bivariate analysis (Spearman rank correlation). Quantitative research results found that the value of each variable is greater than the ρ (rho) table (0.560) at α = 0.05, it shows that there is a relationship between the input components (HR and facilities), process (data collection) and outputs (cross-sectoral feedback) with successful TB surveillance in Regency of Aceh Barat.